A Switching Regression Model for Wage Determinants in the Public and Private Sectors of a Developing Country - van der Gaag, Jacques; Vijverberg, Wim (The Review of Economics and Statistics, 1988)
Jacques van der Gaag, Wim Vijverberg, A Switching Regression Model for Wage Determinants in the Public and Private Sectors of a Developing Country, The Review of Economics and Statistics, Vol. 70, No. 2 (May, 1988), pp. 244-252